Preserving the free education movement in UP Diliman through archival activism - Dela Cruz, Daniel Paulo F.; Olgado, Benedict S. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
After decades of struggle to fight for free education in the university, the student movement finally reached a major milestone of success in the enactment of the Universal Access to Quality Tertiary Education Act. However, looking into the history of the free education movement in the Philippines, it has been realized that there are limited narratives that account for its beginnings and developments. This study explores the role of archival activism in supporting the student movement situated in UP Diliman through an institution-community collaboration. Further, this study emphasized the role of archival practice in providing social power, pursuing social justice, and supporting social memory for these activist groups.
The study utilized archival research and oral history methodology to trace the records and contextualize them through the narratives of the student movement leaders and the university archivist. This methodology also incorporated Moyer's Movement Action Plan (MAP) to map out the obtained facets according to its social movement stage. Tenets of both the university archives and social movement organizations (SMOs) are also analyzed.
Findings of the study show that the university archives is successful in preserving administrative records pertaining to the series of tuition hikes implemented in the university. Contrary to this, the SMOs were only able to preserve records regarding the most recent events in the final stages of the movement as there are no present community archiving initiative on their end. Additionally, the current regulations of the university archives suggest that it would be difficult to push for a collaboration that works around their policies. With the identified realities and challenges, the study explores on possible alternatives of collaboration and eventually calling for an independent student movement archive.
Thesis
Keywords: Social movements; Student movements -- History